Analisis Penggambaran Unsur Magis dalam Film Animasi Cinderella dan Frozen (Kajian Sastra Bandingan) - Salsabila, Dinda Iqlima; Falah, Fajrul (Fakultas Ilmu Budaya Universitas Diponegoro, 2024)
The research presents a comparison between two Walt Disney animated films, namely the animated films Cinderella and Frozen. The research aims to provide an analysis of intrinsic elements and magical elements that can be compared using a comparative literature approach from Sapardi Djoko Damono's theory. The research was carried out through several stages, namely the planning stage, the implementation stage, and the reporting stage. Data collection techniques are carried out by reading, recording, and documenting processes. The data search focuses on intrinsic elements in the form of setting, characters and characterization, as well as themes used in the animated films Cinderella and Frozen. The analysis is reviewed using qualitative research methods and comparative descriptive writing techniques which will present a comparative discussion of data from a literary work in the form of a film. The results of the research show that there are similarities and differences in the selection of intrinsic elements of background, characters and characterization, themes, as well as realism of magical elements used in the animated films Cinderella and Frozen.Keywords: comparative literature, magical, animated film, cinderella, frozen. Penelitian menyajikan perbandingan antara dua film animasi Walt Disney, yaitu film animasi Cinderella dan Frozen. Penelitian bertujuan untuk memberikan analisis unsur intrinsik dan unsur magis yang dapat saling dibandingkan dengan menggunakan pendekatan sastra bandingan dari teori Sapardi Djoko Damono. Penelitian dilakukan melalui beberapa tahapan, yaitu tahap perencanaan, tahap pelaksanaan, dan tahap pelaporan. Teknik pengumpulan data dilakukan dengan proses pembacaan, pencatatan, dan dokumentasi. Pencarian data berfokus pada unsur intrinsik berupa latar, tokoh dan penokohan, serta tema dalam film animasi Cinderella dan Frozen. Analisis diulas dengan metode penelitian kualitatif dan teknik penulisan deskriptif komparatif yang akan memaparkan pembahasan komparatif dari data-data karya sastra berupa film. Hasil penelitian menunjukkan bahwa terdapat persamaan dan perbedaan pemilihan unsur intrinsik latar, tokoh dan penokohan, tema, serta realisme unsur magis yang digunakan dalam film animasi Cinderella dan Frozen.Kata kunci: sastra bandingan, magis, film animasi, cinderella, frozen.